Prenatal exposure to nitrosatable drugs, vitamin C, and risk of selected birth defects. Issue 8 (28th May 2013) - Shinde, Mayura U.; Vuong, Ann M.; Brender, Jean D.; Werler, Martha M.; Kelley, Katherine E.; Huber, John C.; Sharkey, Joseph R.; Zheng, Qi; Suarez, Lucina; Langlois, Peter H.; Canfield, Mark A.; Romitti, Paul A.; et al.
BACKGROUND Nitrosatable drugs, such as secondary or tertiary amines and amides react with nitrite in an acidic environment to form N‐nitroso compounds, teratogens in animal models. Vitamin C is a known nitrosation inhibitor. METHODS Using data from the National Birth Defects Prevention Study, we assessed nitrosatable drug exposure and vitamin C intake during the first trimester among 11, 606 case‐mothers of infants with oral clefts, limb deficiencies (LDs), or congenital heart defects and 6807 control‐mothers of infants without major birth defects during 1997–2005. Daily intake of vitamin C was estimated from maternal interviews that elicited information about supplement use and dietary intake. RESULTS With no reported use of nitrosatable drugs as the referent group, a lower odds ratio (OR) was observed for transverse LDs among births to mothers exposed to secondary amine drugs and daily vitamin C supplementation (adjusted odds ratio [aOR] 1.2, 95% confidence interval [CI] 0.83–1.8) compared with women taking these drugs and no supplementation (aOR 2.7, 95% CI 1.5–4.6). The OR for longitudinal LDs associated with secondary amine exposure was lower with daily dietary vitamin C intake ≥85 mg (aOR 1.2, 95% CI 0.68–2.0) compared with <85 mg (aOR 1.9, 95% CI 1.2–3.1). Daily vitamin C supplementation in combination with higher dietary vitamin C intake reduced associations between nitrosatable drug exposures and limb deficiencies and atrial septal defects not otherwise specified. CONCLUSION Prenatal dietary and vitamin C supplement intake may diminish the association between nitrosatable drug exposure during pregnancy and selected birth defects. Birth Defects Research (Part A) 97:515‐531, 2013. © 2013 Wiley Periodicals, Inc.